ANALISIS ASUHAN KEPERAWATAN KELUARGA PADA LANSIA DENGAN HIPERTENSI MELALUI KOMBINASI INTERVENSI INOVASI ISOMETRIC HANDGRIP EXERCISE DAN SLOW DEEP BREATHING EXERCISE UNTUK MENURUNKAN TEKANAN DARAH DI RT 003/ RW 005 KELURAHAN LIMO - Alda Amatus Syahidah, (2023)
Hypertension is a health problem that is always increasing every day. Complementary therapy that can be given to reduce blood pressure is isometric handgrip exercise and slow deep breathing exercise. The application of this therapy to the elderly with hypertension in addition to lowering blood pressure can be beneficial in maintaining body muscle mass. This application aims to determine the effectiveness of a combination of isometric handgrip exercise and slow deep breathing exercise in reducing blood pressure in the elderly who suffer from hypertension. This intervention is given 3 times a week for 4 weeks. The results of implementing the intervention for 4 weeks showed a decrease in blood pressure in managed patients from 160/95 mmHg to 130/80 mmHg, while in patients who resumed from 150/100 mmHg to 130/90 mmHg. These results show that the combination of isometric handgrip exercise and slow deep breathing exercise helps reduce blood pressure. Health services are advised to apply a combination of isometric handgrip exercise and slow deep breathing exercise as a complementary therapy for hypertension sufferers